Financial Report Analysis with Trends in Changes in PT Samudera Indonesia's Profitability Ratios - Rahmad Gusrifa (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the financial statements of PT Samudera Indonesia using a trend approach to changes in profitability ratios. The profitability ratios analyzed include Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), which provide an overview of how efficiently a company generates profits relative to assets, equity, and revenue. The data used in this study are PT Samudera Indonesia's financial statements for the last five years, from 2019 to 2023. The analytical method used is quantitative descriptive analysis by calculating changes in profitability ratios each year and identifying trends that occur. The results of the study indicate fluctuations in profitability ratios influenced by internal and external factors of the company, including management policies and market conditions. These findings are expected to provide useful information for stakeholders in making investment decisions and provide recommendations to improve the company's performance in the future.